ChemInform Abstract: Are Alkyne Reductions Chemo‐, Regio‐, and Stereoselective Enough To Provide Pure (Z)‐Olefins in Polyfunctionalized Bioactive Molecules?. Issue 17 (4th April 2013) - Oger, Camille; Balas, Laurence; Durand, Thierry; Galano, Jean‐Marie
Abstract Review: 546 refs.